The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1080/08853901003652344
|View full text |Cite
|
Sign up to set email alerts
|

Trade Policy and Export Diversification: What Should Colombia Expect from the FTA with the United States?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The sectoral concentration of exports has been a continuous concern for governments in developing countries, according to [ 34 ]. Therefore, they promoted the creation of trade agreements to diversify markets, trade partners and increase exports.…”
Section: Literature Review and Contextmentioning
confidence: 99%
“…The sectoral concentration of exports has been a continuous concern for governments in developing countries, according to [ 34 ]. Therefore, they promoted the creation of trade agreements to diversify markets, trade partners and increase exports.…”
Section: Literature Review and Contextmentioning
confidence: 99%
“…The results of the estimation showed that GSP preference to Colombia has a positive impact on exports. Martincus and Gomez (2009) assessed the impact of trade agreements on export diversification. For this purpose, they chose Colombian and US trade agreements and assessed whether Colombia could diversify its exports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Institutions of trade -both multilateral and regional -are most often linked to vulnerability through their function as a mechanism to facilitate trade flows (Martincus and Gomez, 2009;Dennis and Shepherd, 2011). However, as both Mansfield and Reinhardt (2008, on trade policy) and Cadot et al (2009, on agricultural trade policy) point out, they also reduce the volatility of both policy and trade flows.…”
Section: Economic Vulnerability and Tradementioning
confidence: 99%
“…Liberalisation of tariffs and harmonisation of standards have been shown to increase export variety ( e.g. for NAFTA, see Kehoe and Ruhl, 2002; Feenstra and Kee, 2007: Martincus and Gomez, 2009). Extrapolating from evidence on Bilateral Investment Treaties (Neumayer and Spess, 2005), we might also expect that the permanence of market access will decrease risk and may encourage investment in new export sectors.…”
mentioning
confidence: 99%